Biochemical characterization of U2 snRNP auxiliary factor: an essential pre-mRNA splicing factor with a novel intranuclear distribution. - Zamore, P D (1991)
U2 auxiliary factor (U2AF) is a non-snRNP protein required for the binding of U2 snRNP to the pre-mRNA branch site. Purified U2AF comprises two polypeptides of 65 and 35 kd. We have performed biochemical complementation and immunological assays to characterize U2AF in greater detail. First, we use an extract lacking only U2AF activity to show that U2AF is an essential splicing factor. Second, we show that all U2AF activity in vitro resides in the 65 kd U2AF polypeptide. Third, based upon both immunological and functional criteria, we show that U2AF is evolutionarily conserved. Most significantly, a Drosophila melanogaster nuclear extract contains proteins that are antigenically related to both human U2AF polypeptides and can substitute for human U2AF in vitro. Finally, we show that U2AF has an unexpected intranuclear distribution. Although diffusely present throughout the nucleoplasm, U2AF is also concentrated in a small number (between one and five) of nuclear 'centers.' This localization differs strikingly from that reported for snRNP antigens and splicing factors. Our data, in conjunction with those in the accompanying paper [Carmo-Fonseca et al. (1991) EMBO J., 10, 195-206.], suggest that these centers represent novel aspects of nuclear organization.